Nature, man and God in medieval Islam : ʻAbd Allah Baydawi's text, Tawaliʻ al-anwar min mataliʻ al-anzar, along with Mahmud Isfahani's commentary, Mataliʻ al-anzar, sharh Tawaliʻ al-anwar - Bayḍāwī, ʻAbd Allāh ibn ʻUmar, -1286?; Calverley, Edwin Elliott, 1882-1971.; Pollock, James W. (James Wilson), 1922-; Iṣfahānī, Maḥmūd ibn ʻAbd al-Raḥmān, 1275 or 1276-1348 or 1349. (Leiden ; Boston : Brill, 2002)
A contemporary to Thomas Aquinas in Latin Catholic Italy, and with a parallel motivation to stabilize each his own civilization in its flux and storm, 'Abd Allah Baydawi of Ilkhan Persia wrote a compact and memorable Arabic Summation of Islamic Natural and Traditional Theology. With the same strokes of his pen he presented the Islamic version of the Science of Theological Statement, bafflingly called "Kalam" while familiarly embracing "Theology". Baydawi's Tawali'al-Anwar min Matal'al-Anzar (Rays of Dawnlight Outstreaming from Far Horizons of Logical Reasoning), with Mahmud Isfahani's commentary, is a formidably clear logical and mental vision of mankind's final completion as a spiritual structure in Islam. Reality - in nature's Possible mode, in an apodictic Divine mode, and in humanity's heroic Prophetic mode - comprises man's Worldview and is the Theme of the Baydawi/Isfahani discourse. The Edifice of Man and Humanity's evanescent Evidence within it are both hugely arresting and moving. The print edition is available as a set of two volumes (9789004121027)
Preliminary Material / Edwin E. Calverley and James W. Pollock -- Acknowledgments / James W. Pollock -- Translators' Introduction / Edwin E. Calverley and James W. Pollock -- Isfahani's Foreword to His Commentary, Matali' al-Anzar, Sharh L 2, T 2, MS 3b / Edwin E. Calverley and James W. Pollock -- Baydawi's Foreword to His Concise Text, Tawali' al-Anwar min Matali' al-Anzar L 4, T 3 / Edwin E. Calverley and James W. Pollock -- Isfahani says: L 5, T 3, MS 5a / Edwin E. Calverley and James W. Pollock -- Chapter 1: Principles of Epistemology / Edwin E. Calverley and James W. Pollock -- Chapter 2: Explanatory Statements / Edwin E. Calverley and James W. Pollock -- Chapter 3: Argumentation / Edwin E. Calverley and James W. Pollock -- Chapter 4: The Distinguishing Properties of Sound Logical Reasoning / Edwin E. Calverley and James W. Pollock -- Chapter 1: Classification of Things Known / Edwin E. Calverley and James W. Pollock -- Chapter 2: Existence and Nonexistence / Edwin E. Calverley and James W. Pollock -- Chapter 3: Quiddity / Edwin E. Calverley and James W. Pollock -- Chapter 4: Necessity and Possibility, Eternity and Temporality / Edwin E. Calverley and James W. Pollock -- Chapter 5: Singularity and Plurality / Edwin E. Calverley and James W. Pollock -- Chapter 6: Cause and Effect / Edwin E. Calverley and James W. Pollock -- Chapter 1: General Topics / Edwin E. Calverley and James W. Pollock -- Chapter 2: Quantity / Edwin E. Calverley and James W. Pollock -- Chapter 3: Quality / Edwin E. Calverley and James W. Pollock -- Chapter 4: Accidents of Relation / Edwin E. Calverley and James W. Pollock -- Section 3: Substances / Edwin E. Calverley and James W. Pollock -- Chapter 1: Bodies / Edwin E. Calverley and James W. Pollock -- Chapter 2: Incorporeal Substantial Beings / Edwin E. Calverley and James W. Pollock.
Includes bibliographical references (v. 2, pages 1157-1162) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Islam -- Doctrines; Islamic philosophy; Islam -- Doctrines; Philosophie islamique; RELIGION -- Islam -- Theology; Islam -- Doctrines; Islamic philosophy; Islam; Islamitische filosofie